Avoidance of Electrode Related MRI Artifact during Staged Deep Brain Stimulator Implantation - Giller, Cole; Mehta, Shyamal; Yanasak, Nathan; Jenkins, Patrick (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Centers implanting deep brain stimulator (DBS) electrodes on different days often protect the first electrode tip with a protective cap, tunnel it under the scalp, and connect it to the generator at a later procedure. If magnetic resonance imaging (MRI) is used for planning during the second implantation, MRI artifacts from the protective cap could potentially corrupt the stereotactic coordinates. The importance of this problem may increase if emerging MRI safety data lead to more frequent use of MRI for these purposes.Objective To describe an MRI artifact arising from the use of the standard protective DBS cap that corrupts stereotactic planning and to describe a way to avoid the artifact.Methods After noting the artifact during a staged DBS procedure, a nonmetallic silastic sleeve contained in the existing DBS implantation kit was used in nine subsequent patients. Two caps with standard metallic screws were also tested with MRI phantoms.Results The silastic sleeve protected the DBS electrode but did not produce MRI artifact. The phantom studies demonstrated significant artifact from caps containing screws.Conclusion A silastic sleeve provides adequate protection of the DBS electrode during staged implantation and avoids the MRI artifact associated with protective caps with screws.
Keywords: deep brain stimulation; MRI artifact; Parkinson's disease